Silibinin inhibits the fibrotic responses induced by cigarette smoke via suppression of TGF-β1/Smad 2/3 signaling. (August 2017) - Ko, Je-Won; Shin, Na-Rae; Park, Sung-Hyeuk; Lee, In-Chul; Ryu, Jung-Min; Kim, Ha-Jung; Cho, Young-Kwon; Kim, Jong-Choon; Shin, In-Sik
Abstract: Cigarette smoke (CS) is generally accepted as a major contributor to chronic obstructive pulmonary disease (COPD) which is characterized by chronic inflammation, fibrotic response, and airway obstruction. In this study, we investigated the preventive effects of silibinin, an active constitute of silymarin on CS and lipopolysaccharide (LPS) exposure-induced fibrotic response. Mice were exposed to CS for 1 h per day (8 cigarettes per day) for 4 weeks. On day 12 and 26, mice were treated with LPS intranasally. Silibinin (10 or 20 mg/kg) was administered orally 1 h before CS exposure. Silibinin markedly decreased the inflammatory cell count in the bronchoalveolar lavage fluid, and reduced levels of proinflammatory mediators. Silibinin suppressed CS + LPS-induced collagen deposition in lung tissue, as evidenced via immunohistochemistry and Masson's trichrome stain. Additionally, silibinin effectively inhibited CS + LPS-mediated expression of transforming growth factor-β1 (TGF-β1) and Smad 2/3 phosphorylation. Taken together, our data indicate that silibinin effectively inhibits the fibrotic response induced by CS + LPS exposure, possibly via suppression of TGF-β1/Smad 2/3 signaling, which results in reduced collagen deposition. These findings suggest that silibinin has therapeutic potential for the treatment of COPD. Highlights: Protective effect of silibinin on airway fibrotic responses was investigated. Silibinin inhibited inflammatory responses. Silibinin inhibited collagen deposition, which was closely related to downregulation of TGF-β1/Smad 2/3 signaling.